Respuesta :

Answer:

x = -6

Step-by-step explanation:

[tex]x+\frac{2}{3}=\frac{8}{9}x\\\\x = \frac{8}{9}x - \frac{2}{3}\\\\x - \frac{8}{9}x= -\frac{2}{3}\\\\\frac{9}{9}x-\frac{8}{9}x=\frac{2}{3}\\\\\frac{1}{9}x=-\frac{2}{3}\\\\x=-\frac{2}{3}*\frac{9}{1}\\\\x=(-2)*3\\\\x = -6[/tex]

Answer:

x = [tex]\frac{2}{9}[/tex]

Step-by-step explanation:

Given

x + [tex]\frac{2}{3}[/tex] = [tex]\frac{8}{9}[/tex] ( multiply through by 9 to clear the fractions )

9x + 6 = 8 ( subtract 6 from both sides )

9x = 2 ( divide both sides by 9 )

x = [tex]\frac{2}{9}[/tex]